If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -4 = x + -12 Reorder the terms: -4 + 3x = x + -12 Reorder the terms: -4 + 3x = -12 + x Solving -4 + 3x = -12 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -4 + 3x + -1x = -12 + x + -1x Combine like terms: 3x + -1x = 2x -4 + 2x = -12 + x + -1x Combine like terms: x + -1x = 0 -4 + 2x = -12 + 0 -4 + 2x = -12 Add '4' to each side of the equation. -4 + 4 + 2x = -12 + 4 Combine like terms: -4 + 4 = 0 0 + 2x = -12 + 4 2x = -12 + 4 Combine like terms: -12 + 4 = -8 2x = -8 Divide each side by '2'. x = -4 Simplifying x = -4
| -6(k-7)-2(-4k+6)=7k+5k | | 5y=0-15 | | 3(4x-1)(4x+3)=48x | | 4.2+m=8.3 | | 2(8+2n)=32+8 | | 4x+4=-5 | | .0*x= | | 3(x+5)-4=2(4x+5) | | 2x^2+2x^2+16=4x^2-16 | | 5+2u=-5 | | 10(10)4x+2=40 | | 15u-10=-6 | | 7050=70x | | y=16x+9 | | 2x-3x+1=(5x+1) | | -15u-10=-6 | | 0=-9w^2+30w-25 | | (4y-7)(4y+7)= | | 27u-10=42u-6 | | 36/9=4 | | 3(r+2)=-2(3r-3) | | 3(2n-4)-2n=30-6 | | u=3(6n+33)+5(n+1) | | 3+9-(2*3)= | | 1.2x+2.6=0.7x+0.25 | | 5y=0-8 | | 4x^3/2x^2/9 | | 21.3=-4.3+8m | | 0.6=0.83+y | | 6x=-.5y | | 2(3x)+1=(5x+1) | | 2m+17=-(5m-2) |